Clinical significance of smear positivity for acid-fast bacilli after ≥5 months of treatment in patients with drug-susceptible pulmonary tuberculosis. Issue 31 (August 2016) - Kang, Hyung Koo; Jeong, Byeong-Ho; Lee, Hyun; Park, Hye Yun; Jeon, Kyeongman; Huh, Hee Jae; Ki, Chang-Seok; Lee, Nam Yong; Koh, Won-Jung
Abstract : Abstract: Patients with pulmonary tuberculosis (TB) with acid-fast bacilli (AFB)-positive sputum smear at 5 months or later during treatment are considered to be cases of treatment failure according to World Health Organization guidelines. This study evaluated the proportion, clinical characteristics, and significance of positive sputum smears after ≥5 months of standard treatment in patients with drug-susceptible pulmonary TB. This was a retrospective cohort study of 1611 patients with culture-confirmed drug-susceptible pulmonary TB who received standard anti-TB treatment from January 2009 to February 2014. Forty-one patients (2.5%) who were smear-positive after ≥5 months of treatment and 123 age- and sex-matched control patients were evaluated. Among the 41 smear-positive patients, culture of the sputum specimens yielded Mycobacterium tuberculosis (MTB) in 1 patient (2.4%), nontuberculous mycobacteria (NTM) in 7 (17.1%), and no growth in the remaining 33 patients (80.5%). Treatment was successfully completed in 40 patients (97.6%) with prolongation of the continuation phase regimens without change to second-line anti-TB treatment. In patients with smear positivity after ≥5 months of treatment compared with controls, cavitation on chest radiographs (53.7% vs. 25.2%, P = 0.001), bilateral involvement (51.2% vs. 30.1%, P = 0.01) and combined pleural effusion (26.8% vs. 10.6%, P = 0.01) were found more frequently at the time of treatment initiation, and paradoxical response occurred more commonly (19.5% vs. 3.3%, P = 0.002) during treatment. Smear-positive sputum after ≥5 months of standard anti-TB treatment was mainly because of nonviable MTB bacilli or NTM in patients with drug-susceptible pulmonary TB. AFB smear alone should not be used to assess treatment failure and careful examination of microbiologic status, including culture and drug susceptibility testing, is needed before making changes to retreatment regimens or empirical second-line anti-TB regimens in these patients.